FLP‐Catalyzed Transfer Hydrogenation of Silyl Enol Ethers - Khan, Imtiaz (Angew Chem Int Ed Engl, 2018)
Herein we report the first catalytic transfer hydrogenation of silyl enol ethers. This metal free approach employs tris(pentafluorophenyl)borane and 2,2,6,6‐tetramethylpiperidine (TMP) as a commercially available FLP catalyst system and naturally occurring γ‐terpinene as a dihydrogen surrogate. A variety of silyl enol ethers undergo efficient hydrogenation, with the reduced products isolated in excellent yields (29 examples, 82 % average yield).